Westonci.ca makes finding answers easy, with a community of experts ready to provide you with the information you seek. Join our platform to connect with experts ready to provide detailed answers to your questions in various areas. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
y = 1/2x + 3
change x and y
x = 1/2y + 3
now find the value of y and that is inverse function
x - 3 =1/2 y
y = 2x- 6
f-(x) = 2x - 6
for both domain : ( - ∞ , + ∞ )
range f (x) : ( - ∞ , + ∞ ) - { 0 }
range f-(x) :( -∞ , +∞)
change x and y
x = 1/2y + 3
now find the value of y and that is inverse function
x - 3 =1/2 y
y = 2x- 6
f-(x) = 2x - 6
for both domain : ( - ∞ , + ∞ )
range f (x) : ( - ∞ , + ∞ ) - { 0 }
range f-(x) :( -∞ , +∞)
To find the inverse function you need to change [tex]f(x)[/tex] (call it [tex]y[/tex]) and [tex]x[/tex], then solve for [tex]y[/tex]:
[tex]y = \frac{1}{2}x+3 \\ x = \frac{1}{2}y + 3 \\ x - 3 = \frac{1}{2}y \\ 2x-6 = y[/tex]
So now you have [tex]f^{-1}(x) = 2x-6[/tex].
Composition to prove inverse relation: [tex]f \circ f^{-1} (x) = x[/tex]:
[tex]f(f^{-1}(x)) = \frac{1}{2}(2x-6)+3 = x - 3 + 3 = x \square[/tex]
Domain and Range of both functions is Real numbers since they are both linear equations.
[tex]y = \frac{1}{2}x+3 \\ x = \frac{1}{2}y + 3 \\ x - 3 = \frac{1}{2}y \\ 2x-6 = y[/tex]
So now you have [tex]f^{-1}(x) = 2x-6[/tex].
Composition to prove inverse relation: [tex]f \circ f^{-1} (x) = x[/tex]:
[tex]f(f^{-1}(x)) = \frac{1}{2}(2x-6)+3 = x - 3 + 3 = x \square[/tex]
Domain and Range of both functions is Real numbers since they are both linear equations.
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.